2009
DOI: 10.1089/thy.2008.0270
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Affecting Neck Lymph Node Recurrence and Distant Metastasis in Papillary Microcarcinoma of the Thyroid: Results of a Study in 445 Patients

Abstract: Total thyroidectomy seems advisable in PMC with extrathyroidal extension and neck lymph node metastasis at presentation. Capsular invasion without extrathyroidal extension may suggest aggressive tumor behavior and require radical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
152
5
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(189 citation statements)
references
References 47 publications
17
152
5
9
Order By: Relevance
“…In our study, 32.6% of PTMC patients was found multifocality, and 45.2% of them had central LNM, which , in univariate analysis, was significantly higher than unifocal (p=0.002). This was similar to the results of prior studies, which reported PTMC multifocality was found in 20% to 40% of PTMC patients, 40% to 70% of whom had LNM (Mercante et al,2009 ;Connor et al, 2011;Dunki-Jacobs et al, 2012). However, in multivariate analysis, there was no significant difference in the rate of CLNM between unifocal and multifocal group (p=0.189).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 32.6% of PTMC patients was found multifocality, and 45.2% of them had central LNM, which , in univariate analysis, was significantly higher than unifocal (p=0.002). This was similar to the results of prior studies, which reported PTMC multifocality was found in 20% to 40% of PTMC patients, 40% to 70% of whom had LNM (Mercante et al,2009 ;Connor et al, 2011;Dunki-Jacobs et al, 2012). However, in multivariate analysis, there was no significant difference in the rate of CLNM between unifocal and multifocal group (p=0.189).…”
Section: Discussionsupporting
confidence: 90%
“…Patients with PTC have excellent prognosis; however, the presence of LNM significantly increases the risk of locoregional recurrence, and some groups have demonstrated decreased disease‐free survival rate and increased mortality associated with regional LNM 4, 5, 6, 7, 8, 9, 10. Extensive LND has the potential to decrease regional recurrence and increase disease‐free survival, but may lead to clinically important postoperative morbidities 13, 14, 15.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical LNM in PTC have been identified as an independent risk factor for regional recurrence 4, 5, 6, 7, and emerging evidences from large population‐based studies have indicated decreased disease‐free survival rate and increased mortality associated with regional LNM 7, 8, 9, 10. There is universal agreement that therapeutic lateral neck dissection (LND) should be undertaken in patients with PTC and clinically lateral LNM (LLNM) on the basis of palpation or imaging examination 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Add to this some would argue that in case of CLN metastases, there would also be metastases at level VII; thus CLND would not be sufficient treatment. 15 This study aimed to compare the outcome of pCLND versus no dissection in case of PTC with N0 neck.…”
Section: Introductionmentioning
confidence: 99%